2014
DOI: 10.1175/jhm-d-13-0121.1
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating an Urban Irrigation Module into the Noah Land Surface Model Coupled with an Urban Canopy Model

Abstract: The current research examines the influence of irrigation on urban hydrological cycles through the development of an irrigation scheme within the Noah land surface model (LSM)-Single Layer Urban Canopy Model (SLUCM) system. The model is run at a 30-m resolution for a 2-yr period over a 49 km 2 urban domain in the Los Angeles metropolitan area. A sensitivity analysis indicates significant sensitivity relative to both the amount and timing of irrigation on diurnal and monthly energy budgets, hydrological fluxes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 40 publications
(54 reference statements)
0
67
0
Order By: Relevance
“…This module runs within the Noah LSM and simulates urban irrigation by updating the topsoil layer moisture content for irrigated pixels, to a certain percentage of soil saturation (irrigation demand factor) at a specified irrigation interval. Irrigated soil moisture (SMC IRR ; m 3 m −3 ), soil moisture deficit (DEF; m 3 m −3 ), and irrigation water (IRR; kg m −2 s −1 ) are calculated for the pervious portion of each grid pixel using equations (adopted from Vahmani and Hogue []). normalSnormalMnormalCnormalInormalRnormalR=αnormalSnormalMnormalCmax normalDnormalEnormalF=normalmax[],SMCIRRSMC10 normalInormalRnormalR=ρwnormalΔtnormalDnormalEnormalFD1 where SMC 1 (m 3 m −3 ) and SMC max (m 3 m −3 ) are actual and saturation soil moisture contents, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This module runs within the Noah LSM and simulates urban irrigation by updating the topsoil layer moisture content for irrigated pixels, to a certain percentage of soil saturation (irrigation demand factor) at a specified irrigation interval. Irrigated soil moisture (SMC IRR ; m 3 m −3 ), soil moisture deficit (DEF; m 3 m −3 ), and irrigation water (IRR; kg m −2 s −1 ) are calculated for the pervious portion of each grid pixel using equations (adopted from Vahmani and Hogue []). normalSnormalMnormalCnormalInormalRnormalR=αnormalSnormalMnormalCmax normalDnormalEnormalF=normalmax[],SMCIRRSMC10 normalInormalRnormalR=ρwnormalΔtnormalDnormalEnormalFD1 where SMC 1 (m 3 m −3 ) and SMC max (m 3 m −3 ) are actual and saturation soil moisture contents, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the current analysis, irrigation is assumed to be automatic and with no water loss (fully effective), and irrigation water is added at 02:00 A.M. (local time) to avoid large solar radiation flux periods. Over the Los Angeles metropolitan area, Vahmani and Hogue [] reported that an irrigation demand factor of 65% and an application interval of 3 days represent Los Angeles irrigation behavior with a reasonable accuracy based on prior analysis of monthly water consumption records and monthly outdoor water use estimates for 2003 and 2004. In the current study, an irrigation demand factor of 0.65 with an irrigation rate of 3 times per week is adopted, which is consistent with water restrictions implemented by the Los Angeles Department of Water and Power in 2010 [ Mini et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a flood irrigation parameterization with two different triggering thresholds resulted in up to 80 W m −2 difference in average seasonal latent heat flux increase in the US central Great Plains (Lawston et al, 2015). In another case, Vahmani and Hogue (2014) tested several irrigation demand factors and irrigation timing in their urban irrigation module, finding fluxes, runoff, and irrigation water are sensitive to both inputs. Additionally, the same parameterization used in a different model (Kueppers et al, 2008;Tuinenburg et al, 2014) or in the same model but at a different resolution (Sorooshian et al, 2011) has also produced different coupled atmospheric impacts.…”
Section: Irrigation Physicsmentioning
confidence: 99%
“…However, datasets required for evaluation, such as irrigation amount, irrigation timing, and co-located continuous soil moisture observations, are not widely available, making it difficult to evaluate irrigation schemes (Kueppers et al, 2007). Modeling studies that have included some assessment of the irrigation scheme have used comparisons to annual water withdrawals for irrigation (Lobell et al, 2009;Pokhrel et al, 2012), outdoor water use (Vahmani and Hogue, 2014), recommended amounts of irrigation (Sorooshian et al, 2011(Sorooshian et al, , 2012, or irrigation water usage reported by the US Geological Survey (Ozdogan et al, 2010). Bulk estimates such as these are often not used for robust evaluation but rather indicate that the simulated results are reasonable.…”
Section: Evaluation Of Irrigation In Lsmsmentioning
confidence: 99%
See 1 more Smart Citation